2006
DOI: 10.1177/00222194060390030601
|View full text |Cite
|
Sign up to set email alerts
|

Solving Arithmetic Word Problems

Abstract: This study was designed to determine a word problem difficulty classification in children with arithmetic learning disabilities (ALD; n = 104) in comparison with typically achieving students (n = 44). We tested variables such as (a) semantic structure (Change, Combine, Compare, and Equalize), (b) operation (subtraction and addition), and (c) position of the unknown quantity in the problem. Facet theory with multidimensional scaling techniques (MINISSA) was used to analyze the underlying dimensions in the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 35 publications
5
18
2
1
Order By: Relevance
“…Therefore, our findings verify and extend the literature on the importance of the position of the unknown. Past research has demonstrated that bare or word problems with the unknown at the start are harder than corresponding problems with the unknown at the end (De Corte and Verschaffel 1981Verschaffel , 1987García et al 2006;Hiebert 1982). Our results show that the same occurs in pictorial problems.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Therefore, our findings verify and extend the literature on the importance of the position of the unknown. Past research has demonstrated that bare or word problems with the unknown at the start are harder than corresponding problems with the unknown at the end (De Corte and Verschaffel 1981Verschaffel , 1987García et al 2006;Hiebert 1982). Our results show that the same occurs in pictorial problems.…”
Section: Discussionsupporting
confidence: 68%
“…+ 2 = 5), the problems with the unknown at the start are harder to solve than the ones with the unknown at the end (De Corte and Verschaffel 1981;Hiebert 1982). The same holds for word problems (De Corte and Verschaffel 1987;García et al 2006;Hiebert 1982). But it is unclear whether this result holds for pictorial problems too.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Only for the subtype of compare problems with the unknown compared set was the mediation effect complete. For this subtype, which is easier than the unknown referent set subtype but harder than the unknown difference set subtype (e.g., Garcia et al, 2006; Morales et al, 1985; Riley & Greeno, 1988), the instructional focus on relational terminology appeared to provide adequate scaffolding, in and of itself, for promoting student success. Perhaps these problems of moderate difficulty, relative to the other two subtypes, were closer to the students’ zone of proximal development.…”
Section: Discussionmentioning
confidence: 99%
“…How many more animals does Rose have than Maury?). Compare problems are more difficult than combine or change problems for primary-grade students, even though the calculations required for all three problem types is similar (e.g., Briars & Larkin, 1984; Carpenter, & Moser, 1984; Cummins et al, 1988; De Corte, Verschaffel, & Verschueren, 1982; Garcia, Jimenez, & Hess, 2006; Morales et al, 1985; Powell et al, 2009; Riley & Greeno, 1988; Verschaffel, 1994). Compare problems are the most difficult problem type for two reasons.…”
Section: Compare Problems and Relational Terminologymentioning
confidence: 99%
See 1 more Smart Citation